The 2D metallicity distribution and mixing scales of nearby galaxies - Williams, Thomas G.; Kreckel, Kathryn; Belfiore, Francesco; Groves, Brent; Sandstrom, Karin M.; Santoro, Francesco; Blanc, Guillermo A.; Bigiel, Frank; Boquien, Médéric; Chevance, Mélanie; Congiu, Enrico; Emsellem, Eric; et al. (Monthly notices of the Royal Astronomical Society, 2021)
Understanding the spatial distribution of metals within galaxies allows us to study the processes of chemical enrichment and mixing in the interstellar medium. In this work, we map the 2D distribution of metals using a Gaussian Process Regression (GPR) for 19 star-forming galaxies observed with the Very Large Telescope/Multi Unit Spectroscopic Explorer (VLT-MUSE) as a part of the PHANGS-MUSE survey. We find that 12 of our 19 galaxies show significant 2D metallicity variation. Those without significant variations typically have fewer metallicity measurements, indicating this is due to the dearth of ${\rm H\, {\small II}}$ regions in these galaxies, rather than a lack of higher-order variation. After subtracting a linear radial gradient, we see no enrichment in the spiral arms versus the disc. We measure the 50 per cent correlation scale from the two-point correlation function of these radially subtracted maps, finding it to typically be an order of magnitude smaller than the fitted GPR kernel scale length. We study the dependence of the two-point correlation scale length with a number of global galaxy properties. We find no relationship between the 50 per cent correlation scale and the overall gas turbulence, in tension with existing theoretical models. We also find more actively star-forming galaxies, and earlier type galaxies have a larger 50 per cent correlation scale. The size and stellar mass surface density do not appear to correlate with the 50 per cent correlation scale, indicating that perhaps the evolutionary state of the galaxy and its current star formation activity is the strongest indicator of the homogeneity of the metal distribution.